Building cost management strategy at industrial enterprise: theoretical and methodical aspects - N. Y. Radionova (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2018)
Cost management is a central issue in business planning at industrial enterprises, because it contributes to business performance, financial and economic stability of an industrial enterprise at the market. This raises the importance of studies devoted to theoretical and methodic aspects of cost management strategy at industrial enterprises. The article aims to provide theoretical substantiation to methodical aspects of cost management strategy at an industrial enterprise.Cost management can be defined as a complex of efforts related with the formation and control of costs in course of business operation, aiming at optimization of costs in all the subsystems of an industrial enterprise.Subject to analysis is a set of strategic tasks to be addressed by an industrial enterprise; links between goals and basic components of cost management strategy at an industrial enterprise; correlations between costs, output and profit rates, effects of the ratio of fixed costs to variable costs for the break-even position; the algorithm for calculating the unit profitability. Product features with commercialization effects have essential role in selecting a cost management strategy; they can be assessed by target costing, which detailed review is given. The study demonstrates that a cost management strategy at an industrial enterprise, once properly selected, will be an important factor for its performance and market competitiveness.